Grapevine virus T diversity as revealed by full-length genome sequences assembled from high-throughput sequence data. - Shaheen Nourinejhad Zarghani; Jean Michel Hily; Miroslav Glasa; Armelle Marais; Thierry Wetzel; Chantal Faure; Emmanuelle Vigne; Amandine Velt; Olivier Lemaire; Jean Michel Boursiquot; Arnela Okic; Ana Belén Ruiz-Garcia; et al. (PLoS ONE)
RNASeq or double-stranded RNA based approaches allowed the reconstruction of a total of 9 full-length or near full-length genomes of the recently discovered grapevine virus T (GVT). In addition, datamining of publicly available grapevine RNASeq transcriptome data allowed the reconstruction of a further 14 GVT genomes from five grapevine sources. Together with four GVT sequences available in Genbank, these novel sequences were used to analyse GVT diversity. GVT shows a very limited amount of indels variation but a high level of nucleotide and aminoacid polymorphism. This level is comparable to that shown in the closely related grapevine rupestris stem pitting-associated virus (GRSPaV). Further analyses showed that GVT mostly evolves under conservative selection pressure and that recombination has contributed to its evolutionary history. Phylogenetic analyses allow to identify at least seven clearly separated groups of GVT isolates. Analysis of the only reported PCR GVT-specific detection primer pair indicates that it is likely to fail to amplify some GVT isolates. Taken together these results point at the distinctiveness of GVT but also at the many points it shares with GRSPaV. They constitute the first pan-genomic analysis of the diversity of this novel virus.